Anterior Cerebral Artery Dissection Leading to Severe Subarachnoid Hemorrhage in a Post-Pandemic COVID-19 Patient: A Case Report and a Call for Continued Vigilance - Hanai, Sho; Yanaka, Kiyoyuki; Saura, Minami; Takahashi, Toshihide; Aiyama, Hitoshi; Marushima, Aiki; Ishikawa, Eiichi (Asian Journal of Neurosurgery, 2025)
Coronavirus disease 2019 (COVID-19) can lead to systemic vascular complications, such as endothelial damage and hypercoagulability. Although COVID-19-associated nonaneurysmal subarachnoid hemorrhage (SAH) has been reported, cases involving anterior cerebral artery (ACA) dissection, particularly in the A1 segment, are extremely rare. A 57-year-old man with a recent COVID-19 infection was brought to the emergency department in an unconscious state. Imaging revealed diffuse SAH, and computed tomography angiography identified dissection of the right ACA A1 segment. Urgent surgical intervention with clipping of the dissected segment was performed. Although the patient initially stabilized postoperatively, he subsequently developed severe cerebral infarction, leading to progressive neurological decline. Despite intensive care, the patient succumbed to these complications 10 days after the initial presentation. Although the overall threat of COVID-19 has diminished, vigilance is still required because its vascular complications remain potentially fatal. COVID-19-associated SAH may have a higher mortality rate due to mechanisms distinct from saccular aneurysm rupture, such as arterial dissection and systemic effects. Dissecting an aneurysm of the A1 segment of the ACA is an extremely rare but serious complication, and its management remains challenging. Further studies are required to understand and mitigate COVID-19-related vascular pathologies.
Keywords: COVID-19; subarachnoid hemorrhage; dissection; anterior cerebral artery; clipping